2015
DOI: 10.1111/jon.12207
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Apolipoprotein E4 Polymorphism on the Gray Matter Volume and the White Matter Integrity in Subjective Memory Impairment without White Matter Hyperintensities: Voxel‐Based Morphometry and Tract‐Based Spatial Statistics Study under 3‐Tesla MRI

Abstract: Our findings suggest that the ApoE ε4 is associated with both atrophy of GM volume and disruption of WM integrity in SMI without WMH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…Despite our data were collected at mutlicentric level in a non-homogenized clinical settings using different DTI acquisition protocols, our findings are generally consistent with previous DTI studies, showing alterations of cerebral WM in elderly APOE ε4+ compared with APOE ε4individuals (Persson et al, 2006, Smith et al, 2010, Heise et al, 2011, Ryan et al, 2011. We found a lower WM integrity in individuals carrying APOE ε4 in WM tracts characteristically associated with early AD pathology, such as the corpus callosum, the cingulum, and the inferior longitudinal and fronto-occipital fasciculi (Medina et al, 2006, Rose et al, 2006, Xie et al, 2006, Firbank et al, 2007, Huang et al, 2007, Sydykova et al, 2007, Filippini et al, 2009, Tsao et al, 2014, Lee et al, 2016. In particular, in agreement with previous evidence, we found lower FA and higher radD values in ε4 carriers compared to non-carriers in the genu and splenium of corpus callosum (Persson et al, 2006, Smith et al, 2010, Ryan et al, 2011, Adluru et al, 2014, Tsao et al, 2014, Lee et al, 2016.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite our data were collected at mutlicentric level in a non-homogenized clinical settings using different DTI acquisition protocols, our findings are generally consistent with previous DTI studies, showing alterations of cerebral WM in elderly APOE ε4+ compared with APOE ε4individuals (Persson et al, 2006, Smith et al, 2010, Heise et al, 2011, Ryan et al, 2011. We found a lower WM integrity in individuals carrying APOE ε4 in WM tracts characteristically associated with early AD pathology, such as the corpus callosum, the cingulum, and the inferior longitudinal and fronto-occipital fasciculi (Medina et al, 2006, Rose et al, 2006, Xie et al, 2006, Firbank et al, 2007, Huang et al, 2007, Sydykova et al, 2007, Filippini et al, 2009, Tsao et al, 2014, Lee et al, 2016. In particular, in agreement with previous evidence, we found lower FA and higher radD values in ε4 carriers compared to non-carriers in the genu and splenium of corpus callosum (Persson et al, 2006, Smith et al, 2010, Ryan et al, 2011, Adluru et al, 2014, Tsao et al, 2014, Lee et al, 2016.…”
Section: Discussionsupporting
confidence: 90%
“…We found a lower WM integrity in individuals carrying APOE ε4 in WM tracts characteristically associated with early AD pathology, such as the corpus callosum, the cingulum, and the inferior longitudinal and fronto-occipital fasciculi (Medina et al, 2006, Rose et al, 2006, Xie et al, 2006, Firbank et al, 2007, Huang et al, 2007, Sydykova et al, 2007, Filippini et al, 2009, Tsao et al, 2014, Lee et al, 2016. In particular, in agreement with previous evidence, we found lower FA and higher radD values in ε4 carriers compared to non-carriers in the genu and splenium of corpus callosum (Persson et al, 2006, Smith et al, 2010, Ryan et al, 2011, Adluru et al, 2014, Tsao et al, 2014, Lee et al, 2016. This finding also agrees with prior MRI studies observing macroscopic WM lesions in both normal aging (Bartzokis, 2004, Filippini et al, 2009 and AD patients (Janowsky et al, 1996, Teipel et al, 2003 in the corpus callosum.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, genetic risk factors may aggravate degeneration in individuals with SCD. For instance, compared with noncarriers, ApoE ɛ4 carriers in SCD populations showed lower FA in the splenium of the corpus callosum and the anterior corona radiata [ 117 ]. Another investigation categorized individuals with SCD into a high-risk group and a low-risk group based on age, ApoE genotype, K-MMSE recall score and the Seoul Verbal Learning Test.…”
Section: Structural Mri and Diffusion Mrimentioning
confidence: 99%
“…Combination of these factors classified the temporal atrophy subtype and the minimal atrophy subtype with 73.2% and 76.0% accuracy. Lee et al (2016) [ 117 ] Memory clinic consultation T1 MRI DTI Cross-sectional ApoE ɛ4+: n = 13 (66.4 ± 6.3) ApoE ɛ4-: n = 13 (66.2 ± 7.8) ApoE ɛ4+ SCD showed gray matter atrophy and lower FA compared with ApoE ɛ4- SCD. Rogne et al (2016) [ 69 ] 1 binary question T1 MRI Cross-sectional NC: n = 58 (70.6 ± 6.7) SCD: n = 25 (70.0 ± 9.1) MCI: n = 115 (74.5 ± 7.5) SCD had larger lateral ventricles and smaller hippocampal volumes than NC.…”
Section: Structural Mri and Diffusion Mrimentioning
confidence: 99%
“…3,4 Cross-sectional structural MR imaging studies indicated reduced gray matter in elderly APOE*E4 carriers including healthy controls, subjective memory impairment, mild cognitive impairment (MCI), and AD. [5][6][7][8][9][10][11][12][13][14] In MCI and AD, the APOE*E4-related GM decrease seems to affect areas involved in AD pathology, notably the hippocampus, amygdala, and mesial temporal cortex [14][15][16][17] but also the left occipital, frontal, and anterior cingulate cortices. 14,18 In healthy elderly controls, the APOE*E4 effect on brain structure is less clear.…”
mentioning
confidence: 99%